Int Adv Otol 2021
DOI: 10.5152/iao.2021.21091
|View full text |Cite
|
Sign up to set email alerts
|

Does 3 Tesla Magnetic Resonance Imaging Have Adverse Effect on Cochlear Functions?

Abstract: Objective: The aim of this study was to investigate the effects of 3 Tesla (3T) magnetic resonance imaging (MRI) noise on cochlear functions. Methods: The distortion product otoacoustic emission (DPOAE) test was applied to patients who were scheduled to have 3T MRI in the tertiary care center. Patients who revealed emission amplitudes at all frequencies (1, 1.5, 2, 3, 4, 6, and 8 kHz) in the DPOAE test before MRI were included in the study. After MRI, the DPOAE test was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…While MRI scans without a cochlea implant have been shown to affect the hearing function, relating to the scanner-generated noise exposure at 1.5 T [ 13 ], the additional use of fitted protective headphones limits or excludes the effect on the hearing function [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…While MRI scans without a cochlea implant have been shown to affect the hearing function, relating to the scanner-generated noise exposure at 1.5 T [ 13 ], the additional use of fitted protective headphones limits or excludes the effect on the hearing function [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A less than optimal placement of the hearing protection equipment or a problem in the fitting of the foam canal tip due to an inadequate choice of size for the participant's auditory canal can more probably be linked to some of these observations. Yildirim et al [52] showed that the impact of 3 T MRI noise on DPOAEs was only temporary and located in the higher spectrum of the tested frequencies (2, 6 and 8 kHz). Therefore, we would expect this frequency range to be affected prior to the lower ones [53], which is not our case.…”
Section: Temporary Changes In Hearing Outcomesmentioning
confidence: 99%